2013
DOI: 10.1097/prs.0b013e31829f4a2c
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Causality between Negative Ulnar Variance and Kienböck Disease

Abstract: Risk, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…We applied these criteria to determine the relationship between vitamin C and CRPS similar to health research in other medical specialties. (1416) Strength of association, consistency, specificity, temporality, biological gradient (dose response relationship), biological plausibility, coherence, experimental evidence, and analogy constitute the 9 Hill criteria. (17) We determined a criterion to be met when a definition and explanation of it provided by Hill were valid with vitamin C and CRPS based on the available evidence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied these criteria to determine the relationship between vitamin C and CRPS similar to health research in other medical specialties. (1416) Strength of association, consistency, specificity, temporality, biological gradient (dose response relationship), biological plausibility, coherence, experimental evidence, and analogy constitute the 9 Hill criteria. (17) We determined a criterion to be met when a definition and explanation of it provided by Hill were valid with vitamin C and CRPS based on the available evidence.…”
Section: Methodsmentioning
confidence: 99%
“…We did not find any information about the number of criterion to be met for an association to be considered causal, but we observed that if majority of criteria were met, the authors considered the association to be causal. (1416) In addition, there was a lack of information about the weightage of individual criterion. In the preparation of this manuscript, the authors adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Although there is no published research to indicate that PLFD does not alter the UV individually in the absence of distal radius fracture, numerous studies implicated possible role of UV in the pathogenesis of Kienbock’s disease, or instability in the wrist and carpal ligamentous disruption (3, 12-14). …”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by lunate sclerosis, cystic changes, fragmentation and articular surface collapse on plain radiograph [3,4]. It occurs most commonly in men aged 20 to 40 years of age.…”
Section: Introductionmentioning
confidence: 99%